COMMUNICATION STRATEGIES USED BY ENGLISH TEACHER IN TEACHING ENGLISH AS FOREIGN LANGUAGE - Angga Dwinka; Irma Diani; Syafryadin Syafryadin (PROJECT (Professional Journal of English Education), 2021)
The aim of this study is to find out the communication strategies used by English Senior High School Teachers in Bengkulu Tengah. This study belongs to mix method which involved questionnaire and interview to collect the required data. Questionnaire was distributed to 21 teachers who were teaching at the senior high school 2020/2021 academic year. Then interview, was employed to enrich the data. The data were analyzed by using Dornyei & Scott’s (1997) taxonomy of communication strategies. The results show that the English teachers in Bengkulu Tengah more prefer to use communication strategy in the form of prefabricated patterns, nonlinguistic mean and stalling or time gaining. They also try to use those communication strategies in good order from change the word that the student unfamiliar with to familiar word, then they use the body gesture to stress the meaning and last, they use code mix or partial translation to make students get the meaning. The use of those communication strategies is underlying two main reason which are solving the speaking problems and making interactive speaking situation. Teachers employed the various communication strategies to stimulate students to be more active during teaching and learning process. Keywords:  Communication Strategies, English Teacher, Teaching English as Foreign Language